2020
DOI: 10.1002/alr.22685
|View full text |Cite
|
Sign up to set email alerts
|

Pepsin exposure in a non‐acidic environment upregulates mucin 5AC (MUC5AC) expression via matrix metalloproteinase 9 (MMP9)/nuclear factor κB (NF‐κB) in human airway epithelial cells

Abstract: Background Gastric reflux GR is a backflow of gastric content to the aerodigestive tract GR was previously found to be associated with inflammatory airway diseases and a potential cause of airway remodeling Chronic exposure to gastric content may induce damage from nose to lung because digestive enzymes and acidity are toxic to airway epithelial cells Recently the toxicity of pepsin in a non-acidic environment was found to increase proinflammatory cytokines and receptors in the epithelium of the aerodigestive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…MMP‐2,9,14 may be dysregulated by sE‐cad 52 and MMP7 by E‐cad/CTF‐related Wnt signaling 72 . MMP‐9 mediates pepsin‐induced mucin 5AC expression in airway epithelial cells contributing to hypersecretion and inflammation, 73 is induced by TGF‐β signaling in tracheal cells, a key pathway in laryngotracheal stenosis, 74 is elevated in mild and severe GERD, 75 and plays a role in the early inflammatory response in a model of Barrett's esophagus (BE) 76 . MMP‐2, 7 and 9 have been implicated in laryngeal cancer 77 .…”
Section: Discussionmentioning
confidence: 99%
“…MMP‐2,9,14 may be dysregulated by sE‐cad 52 and MMP7 by E‐cad/CTF‐related Wnt signaling 72 . MMP‐9 mediates pepsin‐induced mucin 5AC expression in airway epithelial cells contributing to hypersecretion and inflammation, 73 is induced by TGF‐β signaling in tracheal cells, a key pathway in laryngotracheal stenosis, 74 is elevated in mild and severe GERD, 75 and plays a role in the early inflammatory response in a model of Barrett's esophagus (BE) 76 . MMP‐2, 7 and 9 have been implicated in laryngeal cancer 77 .…”
Section: Discussionmentioning
confidence: 99%
“…Mucus gene expression is increased by reactive oxygen species, cytokines, and inflammatory mediators of respiratory inflammatory diseases [ 3 5 ]. The nature and hypersecretion of the mucus change the course of the disease [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further research on the effects of pepsin on the respiratory tract in non-acidic conditions found that it could induce mucus hypersecretion in both upper and lower airway epithelial cells [ 19 ]. This effect was due to an increase in mucin 5AC expression after exposure to pepsin via the matrix metalloproteinase 9 (MMP9) and phosphorylated nuclear factor κB (NF-κB) pathways.…”
Section: Effects Of Pepsin On the Airwaysmentioning
confidence: 99%